Fagdidaktiske temaer i helsefagene - Knutstad, Unni (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
The aim of this anthology is to present current educational research that draws attention to didactics, more specifically to the need for didactic research in health-related subject areas. The anthology is the result of work within the Learning and Interaction research group at the Faculty of Health Sciences at Oslo Metropolitan University and also includes contributions from partners at University College Copenhagen and Rigshospitalet Copenhagen. The anthology analyzes an educational experiment in which the transition between education and professional practice is the main theme. Furthermore, it explores reflections on key concepts and discussions within subject didactics, such as whether there is too much practical training in nursing education, complexity in clinical work and health communication. Additional themes addressed in the book inlude various teaching activities, such as the use of technology and learning assistants, and local curricula for learning and assessment in practical studies.